Pengaruh Attachment dan Penyesuaian Diri terhadap Self-Esteem Siswa SMP Teuku Umar Semarang Tahun Pelajaran 2019/2020 - Erina Vicky Alfina; Awalya Awalya (Indonesian Journal of Counseling and Development, 2021)
This study aims to determine the effect of attachment and self-adjustment on the self-esteem of Teuku Umar Junior High School students in Semarang Academic Year 2019/2020. Efforts to achieve goals, researchers use this type of quantitative research with ex post facto research designs. In practice, researchers used simple random sampling. Collecting data by spreading attachment scale, adjustment and self-esteem. The validity test used the product moment formula and the reliability test used Cronbach's alpha. The data analysis technique used multiple regression analysis test. The research that has been done has resulted in the level of self-esteem and attachment in the high category. Meanwhile, the level of adjustment is in the medium category. The results of the first hypothesis analysis show that there is a positive and significant effect of attachment on self-esteem. The results of the second hypothesis analysis indicate that there is a positive and significant effect of self-adjustment on self-esteem. The results of the analysis of the third hypothesis can be seen that there is a significant effect of attachment and self-adjustment on self-esteem. The results of this study concluded that the higher the attachment and self-adjustment, the higher the self-esteem of students. The research suggestion from these findings is that guidance and counseling teachers should provide several services that are related to attachment, adjustment and self-esteem by paying attention to student needs. This step is used so that students have more positive attachments, good adjustment in the hope that students have better self-esteem as well